Made in the image of god: the creation of אדם: the commissioning of the king and the chaoskampf of YHWH - Crouch, C.L. (Brill, 2016)
This article suggests that Genesis 1 and Psalms 8, 18 and 89 reflect a mythological tradition which described the creation of the human king as YHWH’s counterpart in the divine battle against chaos. The residual royal features of the narrative of the creation of אדם in Genesis 1—the creation of the אדם in the image of god, to exercise dominion—appear in a context of a polemical revision of YHWH’s Chaoskampf and are suggestive of the older tradition’s inclusion of the king’s commissioning as YHWH’s representative and earthly counterpart in these activities. Psalm 8 similarly associates the creation of a royal figure with the exertion of authority and dominion over chaos, using the same image of god language as Genesis 1 to describe this figure and to articulate his special relationship with YHWH. Psalm 18 and especially Psalm 89 affirm the location of the king’s Chaoskampf commission in the midst of YHWH’s own Chaoskampf activities, with the latter’s use of parental language echoing the image of god language in Genesis 1.